1989
DOI: 10.1111/j.1651-2227.1989.tb11278.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Affinity of Haemoglobin Modulates Cerebral Blood Flow in Premature Infants A Study with the Non‐invasive Xenon‐133 Method

Abstract: Oxygen affinity of haemoglobin modulates cerebral blood flow in premature infants: a study with the non-invasive Xe-133 method. Acta Paediatr Scand Suppl 360: 26, 1989. Low cerebral blood flow (CBF) is thought to cause ischaemic brain lesions in premature infants, but a normal outcome has also been observed. Low oxygen affinity of haemoglobin and high arterial oxygen content, independently, reduce CBF under normal, physiological conditions. Transfusions lower the amount of fetal haemoglobin [HbF] and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 20 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…Considering that the normal value of CBV, evaluated by NIRS, is 2200 mL/ 100 g (SD 400) in healthy preterm infants (16), our measurements indicate a reduction in CBV in our patients of about 5% after blood transfusions, that is of physiologic interest but does not seem to have clinical implications. These results con rm the ndings of Lipp-Zwalhen et al who observed a decrease in CBF in transfused preterm infants through the xenon clearance technique (17). Our data indicate that the observed decrease in DCBV could be due to the increase in cerebrovascular resistance, as re ected by the decrease in DV and by the increased RI, probably favoured by the vasoconstricting effect of the increased cerebral oxygen supply and/or viscosity of the blood after the transfusions (4, 5).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Considering that the normal value of CBV, evaluated by NIRS, is 2200 mL/ 100 g (SD 400) in healthy preterm infants (16), our measurements indicate a reduction in CBV in our patients of about 5% after blood transfusions, that is of physiologic interest but does not seem to have clinical implications. These results con rm the ndings of Lipp-Zwalhen et al who observed a decrease in CBF in transfused preterm infants through the xenon clearance technique (17). Our data indicate that the observed decrease in DCBV could be due to the increase in cerebrovascular resistance, as re ected by the decrease in DV and by the increased RI, probably favoured by the vasoconstricting effect of the increased cerebral oxygen supply and/or viscosity of the blood after the transfusions (4, 5).…”
supporting
confidence: 91%
“…Our data indicate that the observed decrease in DCBV could be due to the increase in cerebrovascular resistance, as re ected by the decrease in DV and by the increased RI, probably favoured by the vasoconstricting effect of the increased cerebral oxygen supply and/or viscosity of the blood after the transfusions (4, 5). Nevertheless, it is well known that neonatal CBF is strictly related to foetal haemoglobin concentration (17), and that CBF progressively increases as foetal haemoglobin concentration rises above 30% (5). Transfusions with adult packed red cells cause an elevation of haemoglobin concentration; however, they lower the concentration of foetal haemoglobin and induce a decrease in CBF.…”
mentioning
confidence: 99%
“…Another factor which has to be taken into account is the use of adult red cells for blood transfusion, which will reduce the concentration of fetal haemoglobin, resulting in a decrease of oxygen affinity of haemoglobin. Decreased oxygen affinity of haemoglobin has been shown to result in decreased CBFV [28], CBF [20] and increased cerebral O 2 extraction [29]. It is possible that the expected decrease in oxygen affinity of haemoglobin in our patients might partly explain the decrease in CBFV, but as discussed earlier, it is uncertain whether CBF is also reduced.…”
Section: Discussionmentioning
confidence: 86%
“…We speculate that this might be due to the increased cerebral oxygen and reduced fetal Hb concentration after the transfusion of adult RBCs, which enhance cerebral vessel resistance. 6,8,9,27 However, we did not measure blood viscosity and/or adult and fetal Hb concentrations and therefore we cannot confirm this hypothesis. Thus, these findings suggest that a homeostatic mechanism exists which helps to control cerebral oxygenation by decreasing FOEC and CBF when the oxygen supply is enhanced as occurs after transfusions.…”
Section: Discussionmentioning
confidence: 88%